2008
DOI: 10.1242/jcs.020362
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-catenin signaling causes defects in postnatal cartilage development

Abstract: hypertrophic zones, delayed formation of the secondary ossification center, and reduced skeletal growth. Isolated primary Col2a1-ICAT transgenic chondrocytes showed reduced expression of chondrocyte genes associated with maturation, and demonstrated that VEGF gene expression requires cooperative interactions between BMP2 and β-catenin signaling. Altogether the findings confirm a crucial role for Wnt/β-catenin in postnatal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 31 publications
7
100
0
Order By: Relevance
“…For example, mice conditionally deficient in beta-catenin die before birth 88 . However, transgenic mice expressing the inhibitor of beta-catenin and T cell factor (ICAT) driven by Col2a1 regulatory elements permit the post-natal investigation of beta-catenin downregulation in chondrocytes 89,90 . In these mice, the articular and growth plate chondrocytes show a delay of chondrocyte differentiation with smaller proliferating and hypertrophic zones in the growth plate, decreased chondrocyte proliferation, increased apoptosis, and decreased levels of MMP-13 (which is typically upregulated in OA).…”
Section: Developmental Signaling Pathways In Post Natal Chondrocytesmentioning
confidence: 99%
“…For example, mice conditionally deficient in beta-catenin die before birth 88 . However, transgenic mice expressing the inhibitor of beta-catenin and T cell factor (ICAT) driven by Col2a1 regulatory elements permit the post-natal investigation of beta-catenin downregulation in chondrocytes 89,90 . In these mice, the articular and growth plate chondrocytes show a delay of chondrocyte differentiation with smaller proliferating and hypertrophic zones in the growth plate, decreased chondrocyte proliferation, increased apoptosis, and decreased levels of MMP-13 (which is typically upregulated in OA).…”
Section: Developmental Signaling Pathways In Post Natal Chondrocytesmentioning
confidence: 99%
“…Defects in chondrocyte biology also result in delayed formation of the secondary ossification center that is often observed in chondrodysplastic phenotypes (18)(19)(20). Indeed, the formation of the secondary ossification center in the epiphysis of the Shn2/3-DKO femurs was also delayed (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…However, TG mice misexpressing Dkk1 or Dkk2 in chondrocytes or hypertrophic chondrocytes showed normal development of cartilage and bone. Chen et al (10) found that inhibition of b-catenin activity by chondrocyte-specific overexpression of ICAT (inhibitor of b-catenin and TCF) in mice caused reduced chondrocyte proliferation and differentiation, delayed formation of the secondary ossification center, reduced angiogenesis, and resulted in small skeletal size. However, we found here that misexpression of Dkk1 in chondrocytes or hypertrophic chondrocytes does not cause such defects in TG mice.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9) For instance, chondrocyte-specific inhibition of bcatenin causes defects in postnatal cartilage development. (10)Dkk modulates Wnt signaling by binding to Lrp5 and Lrp6 coreceptors of Wnt. (12) However, there is no direct evidence for a role of Dkk in the coupling of cartilage and bone development with angiogenesis.…”
Section: Introductionmentioning
confidence: 99%